Elucidating the Hot Spot Residues of Quorum Sensing Peptidic Autoinducer PapR by Multiple Amino Acid Replacements - Yehuda, Avishag; Slamti, Leyla; Malach, Einav; Lereclus, Didier; Hayouka, Zvi (Frontiers in Microbiology, 2019)
The quorum sensing (QS) system of Bacillus cereus, an opportunistic human pathogen, utilizes the autoinducing PapR peptide signal that mediates the activation of the pleiotropic virulence regulator PlcR. A set of synthetic 7 mer PapR-derived peptides (PapR7; ADLPFEF) have been shown to inhibit efficiently the PlcR regulon activity and the production of virulence factors, reflected by a loss in hemolytic activity without affecting bacterial growth. Interestingly, these first potent synthetic inhibitors involved D-amino acids or alanine replacements of three amino acids; proline, glutamic acid and phenylalanine of the heptapeptide PapR. To better understand the role of these three positions in PlcR activity, we report herein the second generation design, synthesis, and characterization of PapR7-derived combinations, alternate double and triple alanine and D-amino acids replacement at these positions. Our findings generate a new set of non-native PapR7-derived peptides that inhibit the PlcR regulon activity and the production of virulence factors. Using the amino acids substitution strategy, we revealed the role of proline and glutamic acid on PlcR regulon activation. Moreover, we demonstrated that the D-Glutamic acid substitution was crucial for the design of stronger PlcR antagonists. These peptides represent potent synthetic inhibitors of B. cereus QS and constitute new and readily accessible chemical tools for the study of the PlcR system. Our method might be applied to other quorum sensing systems to design new anti-virulence agents.